Familjeorienterat arbete inom vuxenpsykiatrin - ett område för hälso- och sjukvårdskuratorer - Priebe, Gisela; Afzelius, Maria (Socialmedicinsk tidskrift, 2022)
Since 2010, children’s need for information, advice and support when a parent has a mental illness must be taken into account in health care (HSL 2017: 30, 5:7). For health care professionals, the law supplement states that they need to initiate a family work, where the social worker can have an important role. Today, several suitable family interventions are available, but increased efforts are needed to implement these in the daily work. The aim with the following paper is to illustrate an important field of work for social workers in health care – family oriented work with a focus on children whose parents suffer from mental illness.